(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2015)
Functional analysis is the main tool that assists the behavior analytic therapist in the decisions for more appropriate interventions during the therapeutic process. This article aimed to report the main functional analyzes performed by a therapist during a treatment in child behavior analytic therapy (CBAT). This case was interpreted with more emphasis on functional criteria instead of topographic criteria, and reports a diagnostic process of obsessive-compulsive disorder (OCD) in a five years old child. The target behaviors selected (all being part of the obsessive-compulsive spectrum disorder), functionally analyzed and with good described interventions proposed, decrease their presentation, however, without the pretension to suppress them completely. This case study has shown significant improvement in problem behaviors initially presented by the client, and enabled to verify the effectiveness of the behavior analysis and the chosen interventions.